Thailand : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2001)
Four years since the onset of the financial crisis, Thailand's economic recovery remains fragile and is now threatened by a sharp slowdown in external demand. Bank and corporate sector restructuring policies have formed a key focus of the Article IV discussions. An important initiative to accelerate bank and corporate restructuring is the recent establishment of the Thai Asset Management Corporation (TAMC). An inadequate legal framework has been a major impediment to corporate debt restructuring. Even with an acceleration of bank and corporate restructuring, questions will remain about medium-term growth prospects.